ANALISIS PENGUKURAN KUALITAS LAYANAN PADA JARINGAN 4G - I P Indra Ully Widhi Nugraha; N Gunantara; IGAK Diafari Djuni Hartawan (Program Studi Teknik Elektro UNUD, 2021)
The development of the North Denpasar area, especially the kelurahan and the Peguyanganvillage, has caused many migrants to come and live in the Peguyangan area and have animpact on the development of the population to increase. The population growth of the NorthDenpasar peguyangan region from year to year is growing very rapidly. The analysis methodused in the study